Bahasa Istana Kelantan dari Sudut Sosiolinguistik - Yaacob, Zulkeflee (2009)

(untitled)
The language of the Kelantan royalties is a different language compared to the normal language spoken by the society at large. The language of the royalties specifically that of the Kelantan Malay Royal community is chosen by the researcher because of its uniqueness in the grammar, semantics, vocabulary, phonology and pronounciation. This thesis focuses on the language of the Kelantan royalties from the sociolinguistic perspective, specifically on the etiquette of greeting and addressing. In addition, the social and value system of the society are also studied. The objectives of the study are to identity, clarify and discuss the form of greeting and addressing used in the royal society and its variation and context of use. The language of the Kelantan royalties, which is different from the common language has caused difficulty for most communicators from the multiracial community who are unable to understand nor use the language appropriately. The researcher realizes that effors to document these erudite materials are not done Moreover, the national policy on official languages in Malaysia does not include the royal languages as part of the education. In fact, there is no effort made to learn and frovide awareness of the royal languages as a heritage of the nation for the future generation and the royal languages will be isolated later. Hence, research must be done via the qualitative method such as commodious survey study, observation, participation and interview. To inform the study, a library survey was also conducted. To explain and clarify the language of the Kelantan Royalties, this study utilized the theory by Asmah Hj Omar and Ervin-Tripp on greeting and addressing in order to complement the study from the sociolinguistic perspective. The study showed that the royal community of Kelantan potrays the unique sociolinguistic and cultural traits of the people of Kelantan. There are many forms used for greeting and addressing in the language of the Kelantan royalties. The language also has its unique pronounciation, vocalbulary, pronominal system, phrase and language system. The type of language, vocabulary and context used by the royalties reflect the uniqueness of the identity of the Kelantan Malay society.